(untitled) (AUN INTERNATIONAL CONFERENCE, 2025)
Nigeria faces a deepening convergence of food insecurity and violent conflict, posing significant threats to national stability, livelihoods, and sustainable development. Legal and institutional responses to these dual crises have often been fragmented, reactive, and poorly coordinated. This paper explores how a coherent, integrated governance framework—rooted in robust legal foundations can enhance Nigeria’s capacity to effectively address the complex interplay between food systems and security challenges. The study critically examines existing legal instruments such as the Land Use Act, National Security Agencies Act, Agricultural Promotion Policy, and Disaster Risk Management frameworks. It interrogates the institutional roles and jurisdictional overlaps among federal, state, and local actors tasked with ensuring food security and public safety. Drawing from comparative legal approaches and international best practices, the paper advocates for a harmonized legal architecture that promotes collaboration across sectors, clarity in mandates, and rights-based interventions. Key recommendations include constitutional reforms to clarify responsibilities across tiers of government, the establishment of specialized food-security and conflict-resolution courts or tribunals, and the mainstreaming of environmental and climate-related legal tools. By proposing a more integrated and responsive governance model, this paper contributes to a multidisciplinary dialogue on legal innovation as a strategic pillar for addressing Nigeria’s food and security crises.